2017
DOI: 10.1038/srep45145
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of multi-target receptor tyrosine kinase inhibitors as novel anti-angiogenesis agents

Abstract: Recently, we have identified a biphenyl-aryl urea incorporated with salicylaldoxime (BPS-7) as an anti-angiogenesis agent. Herein, we disclosed a series of novel anti-angiogenesis agents with BPS-7 as lead compound through combining diarylureas with N-pyridin-2-ylcyclopropane carboxamide. Several title compounds exhibited simultaneous inhibition effects against three pro-angiogenic RTKs (VEGFR-2, TIE-2 and EphB4). Some of them displayed potent anti-proliferative activity against human vascular endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Further, reanalysis was performed by specifying the explicit presence of halogen: 79 th position interactions in the All_pose_structure file and the resultant targets were mapped on to the kinome tree Figure 5a. The known wild targets of sorafenib: ABL1 (Kurosu, Ohki, Wu, Kagechika, & Miura, 2009), p38a (Namboodiri et al., 2010), CDK8 (Schneider et al., 2011), MET (Beizaei et al., 2019), TRKB (Kumar et al., 2009), FLT3, FLT1 (Wilhelm et al., 2004), RIPK1 (Martens et al., 2017), DDR1 (El‐Damasy, Cho, Nam, Pae, & Keum, 2016; Kitagawa et al., 2013) and the mutant targets such as JNK2 (functional disability due to this mutation is not reported, hence was considered as wild type; Broecker‐Preuss et al., 2015), BRAF V600E (Wan et al., 2004), KDR T940V (Okamoto et al., 2015), KIT mutant and KIT WT (Wilhelm et al., 2004) were also identified as top‐ranking hits as per the maximal number of interaction patterns, and EphB4 Y774E_A803V_V870I (functional disability due to this mutation is not reported, hence was considered as wild type; Wang et al., 2017), PEK D937N (but wild PEK inhibition is reported [Shiota et al., 2010]), FMS C667T_C830S_C907T (functional disability due to this mutation is not reported, hence was considered as wild type; Uitdehaag et al., 2011; Ullrich et al., 2011) were identified to be mapped on the kinome tree Figure 5a & Table S5. The other targets of sorafenib: CDK2 (WT) and MELK mutant were also found during target prioritization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, reanalysis was performed by specifying the explicit presence of halogen: 79 th position interactions in the All_pose_structure file and the resultant targets were mapped on to the kinome tree Figure 5a. The known wild targets of sorafenib: ABL1 (Kurosu, Ohki, Wu, Kagechika, & Miura, 2009), p38a (Namboodiri et al., 2010), CDK8 (Schneider et al., 2011), MET (Beizaei et al., 2019), TRKB (Kumar et al., 2009), FLT3, FLT1 (Wilhelm et al., 2004), RIPK1 (Martens et al., 2017), DDR1 (El‐Damasy, Cho, Nam, Pae, & Keum, 2016; Kitagawa et al., 2013) and the mutant targets such as JNK2 (functional disability due to this mutation is not reported, hence was considered as wild type; Broecker‐Preuss et al., 2015), BRAF V600E (Wan et al., 2004), KDR T940V (Okamoto et al., 2015), KIT mutant and KIT WT (Wilhelm et al., 2004) were also identified as top‐ranking hits as per the maximal number of interaction patterns, and EphB4 Y774E_A803V_V870I (functional disability due to this mutation is not reported, hence was considered as wild type; Wang et al., 2017), PEK D937N (but wild PEK inhibition is reported [Shiota et al., 2010]), FMS C667T_C830S_C907T (functional disability due to this mutation is not reported, hence was considered as wild type; Uitdehaag et al., 2011; Ullrich et al., 2011) were identified to be mapped on the kinome tree Figure 5a & Table S5. The other targets of sorafenib: CDK2 (WT) and MELK mutant were also found during target prioritization.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Cartoon representation of 42 overlayed ABL1 structures with DFG out -αC out conformations to which imatinib/ponatinib binds. (c) Cartoon representation of six overlayed ABL1 structures with DFG out -αC out conformations which failed to bind with imatinib/ponatinib due difference in Chi-1 torsion angles [Colour figure can be viewed at wileyonlinelibrary.com] considered as wild type; Wang et al, 2017), PEK D937N (but wild PEK inhibition is reported [Shiota et al, 2010]), FMS C667T_C830S_C907T (functional disability due to this mutation is not reported, hence was considered as wild type; Uitdehaag et al, 2011;Ullrich et al, 2011) were identified to be mapped on the kinome tree Figure 5a & Table S5. The other targets of sorafenib: CDK2 (WT) and MELK mutant were also found during target prioritization.…”
Section: Target Identification By Kinomerunmentioning
confidence: 99%
“…Looking ahead, preclinical studies on single inhibitors targeting multiple molecules are being undertaken for both biologicals and SMDs with the dual IL‐4/IL‐13 blocking mAbs against their receptor subunit IL‐4Rα (dupilumab, Table ), with bi‐specific antibodies (eg, dual antagonists for IL‐4/IL‐13, CXCR3/CCR6, and CCR3/CD300a), and with multi‐target receptor tyrosine kinase inhibitors, so far developed for anti‐angiogenic treatment in lung cancer …”
Section: Discussionmentioning
confidence: 99%
“…Many proangiogenic factors have been identified including VEGF, Ang, ephrinB2, and Notch among others. Their receptors, VEGFR‐2, Tie‐2, and EphB4, all belong to the RTK family, which is a subfamily of protein kinases critical to cell growth, survival, and angiogenesis . VEGF is the most potent proangiogenic factor, and its binding to VEGFR‐2 promotes ECs survival, proliferation, and migration.…”
Section: Angiogenic Factors and Compensatory Pathwaymentioning
confidence: 99%
“…Their receptors, VEGFR-2, Tie-2, and EphB4, all belong to the RTK family, which is a subfamily of protein kinases critical to cell growth, survival, and angiogenesis. 41 VEGF is the most potent proangiogenic factor, and its binding to VEGFR-2 promotes ECs survival, proliferation, and migration. Ang and its receptor (Tie-2) are essential for vessel maturation, stabilization, and remodeling of vasculature.…”
Section: Proangiogenic Factorsmentioning
confidence: 99%